Metal‐Specific Biomaterial Accumulation in Human Peri‐Implant Bone and Bone Marrow - Schoon, Janosch; Hesse, Bernhard; Rakow, Anastasia; Ort, Melanie J.; Lagrange, Adrien; Jacobi, Dorit; Winter, Annika; Huesker, Katrin; Reinke, Simon; Cotte, Marine; Tucoulou, Remi; Marx, Uwe; et al. (Advanced science, 2020)
Metallic implants are frequently used in medicine to support and replace degenerated tissues. Implant loosening due to particle exposure remains a major cause for revision arthroplasty. The exact role of metal debris in sterile peri‐implant inflammation is controversial, as it remains unclear whether and how metals chemically alter and potentially accumulate behind an insulating peri‐implant membrane, in the adjacent bone and bone marrow (BM). An intensively focused and bright synchrotron X‐ray beam allows for spatially resolving the multi‐elemental composition of peri‐implant tissues from patients undergoing revision surgery. In peri‐implant BM, particulate cobalt (Co) is exclusively co‐localized with chromium (Cr), non‐particulate Cr accumulates in the BM matrix. Particles consisting of Co and Cr contain less Co than bulk alloy, which indicates a pronounced dissolution capacity. Particulate titanium (Ti) is abundant in the BM and analyzed Ti nanoparticles predominantly consist of titanium dioxide in the anatase crystal phase. Co and Cr but not Ti integrate into peri‐implant bone trabeculae. The characteristic of Cr to accumulate in the intertrabecular matrix and trabecular bone is reproducible in a human 3D in vitro model. This study illustrates the importance of updating the view on long‐term consequences of biomaterial usage and reveals toxicokinetics within highly sensitive organs. Spatially micron‐ and nanoresolved synchrotron X‐ray fluorescence analyses of peri‐implant cancellous bone reveal specific distribution and accumulation patterns of metals released from alloys frequently used in knee and hip arthroplasty. These new insights of the local toxicokinetics of metallic debris prove that cobalt, chromium, and titanium exposure also occurs behind the insulating implant membrane, in the bone and bone marrow.